PENGEMBANGAN INSTRUMEN PENILAIAN KETERAMPILAN SOSIAL MAHASISWA PADA MATA KULIAH MIKRO TEACHING PAI - Amaliyah Amaliyah; Ahmad Hakam; Suci Nur Pratiwi; Sari Wulandari (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
The PAI micro teaching course contains competencies that enable students to empower and implement teacher competencies, including personal, social, pedagogical and professional competencies. This research focuses on developing social skills assessment instruments because: first, the values ​​of social skills are one of the main assets for Islamic Education teacher candidates to interact with the social environment, the second teacher is someone who gives empathy and cares for students. This research aims to describe the steps for developing a social skills assessment instrument and testing the content validity. The research method used the Borg and Gall development model. The process of content validity qualitatively uses peer assessments from PAI lecturers. The process of content validity quantitatively uses the Aikens Index, and the reliability between raters uses the intraclass correlations coefficient. The results of the research describe: first the process and results of content validity qualitatively include suggestions from validators, the second is content validity quantitatively, include the validity and reliability scores.The results of the research are expected: social skills instruments are one of the tools to empower and develop social skills of PAI teacher candidates in learning activities and daily life.